Understanding The Role of Entrepreneurial Ecosystem on Productive Agricultural Entrepreneurship in Bogor Regency Through Structural Equation Modeling - Tapsi, Syhabuddin Al; Baga, Lukman Mohammad; Feryanto, Feryanto (Universitas Muhammadiyah Semarang, 2024)
The engagement of entrepreneurs in the agricultural industry is essential to generate business growth and sustainability through Gross Regional Domestic Product (GRDP). However, the sector contributes less to the GRDP of Bogor Regency. The competence of agricultural entrepreneurs and entrepreneurial ecosystems causes this condition. Meanwhile, productive entrepreneurship can occur through interactions between business owners and their environment. So, this research aimed to analyze the entrepreneurial ecosystem's constructions and role in agricultural entrepreneurship productivity in Bogor Regency. The research used a quantitative approach and followed the Structural Equation Model (SEM) technique. The results of primary data obtained by interviewing 110 respondents using a Likert-scale questionnaire showed that this study strengthens the theory of entrepreneurial ecosystems that empirically contribute to entrepreneurial productivity geographically and in terms of industry specifications. Enhancing high-growth entrepreneurs, increasing income, and growing new businesses are related to entrepreneurial ecosystem’ roles. Hence, reinforcing essential elements of ecosystems was concluded as the practical implications of the findings.